2018
DOI: 10.1016/j.athoracsur.2017.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Complications Drive Unplanned Readmissions After Esophagectomy for Cancer

Abstract: Postoperative occurrence of common complications and prolonged length of stay are associated with unplanned readmission after esophagectomy. Most patients are readmitted within 1 week of discharge. Earlier follow-up after discharge may identify patients with complications and facilitate outpatient intervention to prevent readmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 22 publications
1
25
1
Order By: Relevance
“…Several studies investigated hospital readmission after esophagectomy, with readmission occurring in 11.2% to 18.6% [13,14,[38][39][40]. These rates are higher than the 6.2% found in the current study but many of these studies found post-operative complications to be the biggest risk factor for a readmission.…”
Section: Discussioncontrasting
confidence: 69%
“…Several studies investigated hospital readmission after esophagectomy, with readmission occurring in 11.2% to 18.6% [13,14,[38][39][40]. These rates are higher than the 6.2% found in the current study but many of these studies found post-operative complications to be the biggest risk factor for a readmission.…”
Section: Discussioncontrasting
confidence: 69%
“…It is reported that about 38.1% of the patients experienced ≥ 1 complications within 30 days following esophagectomy; whereas 10.7% of them experienced unplanned readmissions due to inflammation and pulmonary/gastrointestinal complications. [1] Moreover, the pulmonary complications and anastomotic leakage (AL) might result in decreased long-term survival of the patients after esophagectomy. [2] Furthermore, AL is associated with increased morbidity and mortality due to mediastinitis and thoracic contamination.…”
Section: Introductionmentioning
confidence: 99%
“…It may seem intuitive that a potential reverse relationship exists between the hospital stay and readmission rates, where too much emphasis on reducing hospital stay may increase the likelihood of readmission, as some have reported (4). Several other published studies, however, dispute this finding by reporting a higher readmission rate in patients who had a previous longer hospital stay, which reflects the higher morbidity rate in this subgroup of patients (5).…”
mentioning
confidence: 99%